Takṡīr al-Bīah al-Lugawiyyah ‘alā Mahārah al-Kalām laday al-Ṭullāb bi al-Manhaj al-Mukaṡaf - Mustafida, Nur Hidayatul; Mutholib, Abdul (Study Program of Arabic Language Teaching, 2026)
This study was motivated by the limited Arabic-speaking skills of newly enrolled students, highlighting the need for an effective language environment (bī'ah lughawiyyah) supported by an intensive learning program. The study aims to analyze the effect of bi'ah lughawiyyah on students’ Arabic speaking skills (maharah al-kalam), with the Intensive Program serving as an intervening variable at Assalam Bangilan Tuban Islamic Boarding School. A quantitative research approach was employed using path analysis and the Sobel test to examine both direct and indirect effects among the variables. The population of this study consisted of 21 eleventh-grade students at Assalam Islamic Boarding School, Bangilan, Tuban, in the 2025/2026 academic year. Using purposive sampling, 17 students who met the predetermined research criteria were selected as the research sample. Data were collected using a Likert-scale questionnaire to measure implementation of the language environment and the intensive program, and an oral speaking test to assess students’ Arabic speaking proficiency. The findings reveal that the language environment has a significant positive direct effect on students’ speaking skills (β = 0.612; p < 0.05). In contrast, the Intensive Program did not have a significant effect on speaking skills (p > 0.05) and did not function as an intervening variable, as confirmed by the Sobel test (p > 0.05). These findings indicate that a natural, consistent, and communicative language environment plays a more influential role in improving students’ Arabic-speaking skills than formal, intensive instructional programs. The study also suggests that sustained language exposure is essential for developing students’ communicative competence in Arabic.